2009
DOI: 10.1016/j.rmed.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training improves autonomic nervous control in patients with COPD

Abstract: Neural control of heart rate, in addition to other clinically valuable measures, is positively altered in moderate-severe COPD patients following 6 weeks of aerobic exercise training. The improvement in submaximal performance after exercise training was associated with parasympathetic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
5
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 38 publications
3
87
5
6
Order By: Relevance
“…Mixed results have been reported in previous studies examining the effect of exercise on HRV. Variations in exercise doses and intensity of exercise may be responsible for the mixed results across the studies (Borghi-Silva et al, 2009;Carter, Banister, & Blaber, 2003;Okazaki et al, 2005;Sloan et al, 2009). The quantities of work and exercise intensities completed by the participants in the current study were lower than in other research reporting changes in HRV (Carter et al, 2003;Okazaki et al, 2005;Sloan et al, 2009).…”
contrasting
confidence: 62%
“…Mixed results have been reported in previous studies examining the effect of exercise on HRV. Variations in exercise doses and intensity of exercise may be responsible for the mixed results across the studies (Borghi-Silva et al, 2009;Carter, Banister, & Blaber, 2003;Okazaki et al, 2005;Sloan et al, 2009). The quantities of work and exercise intensities completed by the participants in the current study were lower than in other research reporting changes in HRV (Carter et al, 2003;Okazaki et al, 2005;Sloan et al, 2009).…”
contrasting
confidence: 62%
“…However, there is a consistent body of evidence that exercise increases resting vagal cardiac control, in healthy as well as patient groups. 1,[12][13][14][15] Although it is theorized that posture change and an orthostatic challenge may highlight ANS changes better than the resting supine position, 16,17 and that reduced ANS responsiveness to an excitatory stimulus is seen as the most common feature of patho-physiological states, 18 exercise induced changes in HRV during standing and in response to an orthostatic stressor is less known.…”
mentioning
confidence: 99%
“…Georgiopoulou et al and Borghi-Silva et al, reported that under the influence of a pulmonary rehabilitation program, improve heart rate in exercise and lower heart rate at rest. [14][15][16] Borghi-Silva also pointed out that this program beneficial impact on the reduced significantly on ventilation and sensitivity rate. 16 Lacasse et al, says that heart rate at rest is the result of tone is inherent and vagal while the influence of the sympathetic nerve can also be.…”
Section: Discussionmentioning
confidence: 89%
“…[14][15][16] Borghi-Silva also pointed out that this program beneficial impact on the reduced significantly on ventilation and sensitivity rate. 16 Lacasse et al, says that heart rate at rest is the result of tone is inherent and vagal while the influence of the sympathetic nerve can also be. Recent data the researcher shows an imbalance in chronic obstructive pulmonary patients leads to an increased resting heart rate.…”
Section: Discussionmentioning
confidence: 89%